2002
DOI: 10.1086/341095
|View full text |Cite
|
Sign up to set email alerts
|

A Major Susceptibility Locus for Specific Language Impairment Is Located on 13q21

Abstract: Children who fail to develop language normally-in the absence of explanatory factors such as neurological disorders, hearing impairment, or lack of adequate opportunity-are clinically described as having specific language impairment (SLI). SLI has a prevalence of approximately 7% in children entering school and is associated with later difficulties in learning to read. Research indicates that genetic factors are important in the etiology of SLI. Studies have consistently demonstrated that SLI aggregates in fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
194
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(218 citation statements)
references
References 60 publications
13
194
2
5
Order By: Relevance
“…In one study, the subgroup of probands with autism who had no language or clearly impaired language whose parents also had a history of language difficulties were separated from the full sample that included children without language impairment (CLSA, 2001). The linkage signals on two chromosomes, 7q and 13q, both of which have been implicated as loci for SLI (Bartlett, Flax, Logue, Vieland, Bassett, Tallal, & Brzustowicz, 2002;O'Brien, Zhang, Nishimura, Tomblin, & Murray, 2003), were significantly increased, suggesting that these signals were mainly attributable to the language-impaired subtype within autism. Similar findings were obtained in the second study by the Autism Genetic Resource Exchange Consortium (AGRE) using different definitions of language-impaired in an independent sample of autism families (Alarcon et al, 2002).…”
Section: Sample Size and Ascertainmentmentioning
confidence: 99%
“…In one study, the subgroup of probands with autism who had no language or clearly impaired language whose parents also had a history of language difficulties were separated from the full sample that included children without language impairment (CLSA, 2001). The linkage signals on two chromosomes, 7q and 13q, both of which have been implicated as loci for SLI (Bartlett, Flax, Logue, Vieland, Bassett, Tallal, & Brzustowicz, 2002;O'Brien, Zhang, Nishimura, Tomblin, & Murray, 2003), were significantly increased, suggesting that these signals were mainly attributable to the language-impaired subtype within autism. Similar findings were obtained in the second study by the Autism Genetic Resource Exchange Consortium (AGRE) using different definitions of language-impaired in an independent sample of autism families (Alarcon et al, 2002).…”
Section: Sample Size and Ascertainmentmentioning
confidence: 99%
“…14 -16 Noteworthy, also most samples with specific language impairment (SLI) have failed to show any linkage or association signals at the FOXP2 locus, indicating that it is unlikely to play a significant role in cases of typical SLI. 14,17,18 However, one recent study showed putative evidence for association of FOXP2 locus with SLI. 19 In a Finnish dyslexia sample, linkage for 7q31 overlapping SPCH1 and AUTS1 loci was observed, but sequencing of FOXP2 in dyslexic individuals revealed no coding sequence mutations.…”
Section: Introductionmentioning
confidence: 99%
“…) indicates that the conclusions from clinical and psychometric assessment criteria of SLI differ vastly. Clinical approaches may be misleading, particularly in environments with a higher risk of language impairment, for example in families where some degree of speech or language impairment is already present (Bartlett et al, 2002;Bishop, 2006;Gopnik & Crago, 1991).…”
Section: Issues In Specific Language Impairment Assessment Proceduresmentioning
confidence: 99%